SOME FACTORS AFFECTING THE RELATIONSHIP BETWEEN RELIGIOUS GROUPS: A PSYCHOSOCIAL APPROACH - Cemal ÖZEL (Fırat University, 2019)
In this study, we first give some brief information about the concept of religious group and general structures of the religious groups in Turkey. This is followed by an analysis of the common problems between these groups as well as the factors affecting their relationships such as solidarity, competition or conflict, illustrated with various examples from religious groups in Turkey. The factors affecting the relationships between these groups are considered in two groups: “structural factors” and “conjunctural factors”. Structural factors are the ones which are inherent in the nature of a group. These factors apply to all groups. Under this title, we investigate the impact of the sense of belonging, the group’s characteristic structure and the degree of institutionalization of the group on the relationship. Conjunctural factors are related to current conditions. In this section, we discuss if and how the relationship between religious groups is affected by their members’ motives for the participation in the religious group, activities of the group, religious instruction and propaganda one is exposed within the group, the deprivation because of belonging to the group, the priorities and the religious approach of the group, the group’s relationship to political and others forms of power. At the end of the study, it was emphasized the importance of controlling the compulsion of competition, ensuring transparency, fair management of the difference and good operation of control mechanisms as a solution.